Prognostic role of the prognostic nutritional index in patients with pancreatic cancer who underwent curative resection without preoperative neoadjuvant treatment: A systematic review and meta-analysis - Zhao, Pengcheng; Wu, Zuowei; Wang, Zihe; Wu, Chao; Huang, Xing; Tian, Bole (Frontiers in Surgery, 2022)
Background: The prognostic nutrition index (PNI), which has been evaluated in various kinds of cancers, offered a simple yet effective approach to predict the prognosis. The aim of this meta-analysis is to reveal the correlation between preoperative PNI and the prognosis of patients with pancreatic ductal adenocarcinoma (PDAC) who underwent curative resection. Methods: We searched the PubMed, Embase, Web of Science and Cochrane Library databases, and extracted the hazard ratio (HR) with 95% confidential interval (CI) from eligible studies. The pooled HR with 95% CI was applied to evaluate the association between PNI and overall survival (OS), recurrence-free survival (RFS). Results: A total of fourteen studies with 3385 patients were included for meta-analysis. The results (the pooled HR: 1.664, 95% CI: 1.424-1.994, I² =42.6%, p value = 0.046) indicated that low preoperative PNI was closely related to poor OS. In addition, the results suggested that PNI was negatively correlated with RFS (the pooled HR: 1.369, 95%CI: 1.080-1.734). The robustness of these pooled results was verified by our subgroup analysis and sensitivity analysis. Moreover, different cutoff values among studies are responsible for the heterogeneity of pooled HR of OS through meta-regression analysis (p value = 0.042). Funnel plots, Begg's test (p value = 0.228) and Egger′s test (p value = 0.702) indicated no significant publication bias in OS. Conclusion: Preoperative PNI might be a promising marker to predict the prognosis of PDAC patients who underwent curative resection.